Motivational Factors Affecting Iranian English as a Foreign Language (EFL) Learners’ Learning of English Across Differing Levels of Language Proficiency - Bagheri Nevisi, Reza; Farhani, Ala (Frontiers in Psychology, 2022)
The present study aimed at investigating the motivational factors affecting Iranian learners’ learning of English as a Foreign Language across differing levels of language proficiency. To this end, 110 males and 70 females took part in the study and a mixed-methods approach was adopted. First, OPT was administered to determine the proficiency level of the participants and they were placed into three levels of language proficiency: Elementary, intermediate, and advanced. Next, as for the quantitative part of the study, the AMBT questionnaire was distributed among all the participants to delve into the motivational factors. Finally, a semi-structured interview was conducted to qualitatively probe into EFL learners' motivational factors affecting their learning of English. It was found that the motivational factors which encouraged EFL learners resulted from either intrinsic or extrinsic tendencies. The recognized intrinsically-based motivational factors were personal enjoyment, social prestige, and being challenged The extrinsically-oriented factors as the source of motivation toward English learning were getting a job, pursuing education, earning more money, traveling to foreign countries, pursuing academic career, making efficient use of technology, and effectively interacting with native speakers. It was concluded that beginner and intermediate language learners tended to learn English more based on extrinsic factors whereas advanced learners were found to be more intrinsically motivated.